2014
DOI: 10.1016/j.ibusrev.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Economic nationalism and foreign acquisition completion: The case of China

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 63 publications
3
82
0
Order By: Relevance
“…Based on the Thomson Financial M&A database for the period 1982, Zhang, Zhou, and Ebbers (2011 reported that 210,183 deals found to be unsuccessful (460,710 deals completed) out of 670,893 acquisition events. In a recent study, Zhang and He (2014) described that two forces such as nationalistic sentiments grow as a reaction to the instabilities and economic nationalism greatly affects foreign firms' market entry and operations.…”
Section: Theoretical Backdrop: Cross-border Mandasmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the Thomson Financial M&A database for the period 1982, Zhang, Zhou, and Ebbers (2011 reported that 210,183 deals found to be unsuccessful (460,710 deals completed) out of 670,893 acquisition events. In a recent study, Zhang and He (2014) described that two forces such as nationalistic sentiments grow as a reaction to the instabilities and economic nationalism greatly affects foreign firms' market entry and operations.…”
Section: Theoretical Backdrop: Cross-border Mandasmentioning
confidence: 99%
“…More positively, strategy research in emerging economies not only has become an integral part of strategy research in general, but also has led the charge in advancing theories by drawing attention to the context-specific nature of strategic management (Xu & Meyer, 2013). In recent studies, scholars have focused on impact of nationalism and institutional factors on foreign acquisitions success (e.g., Serdar Dinc & Erel, 2013;Zhang et al, 2011;Zhang & He, 2014). Eventually, we capture that cross-border M&As research is relatively young, limited than domestic M&As and other foreign market entry strategies.…”
Section: Comprehensive Review Design: Cross-border Mandasmentioning
confidence: 99%
“…In Barbopoulos et al (2012), Erel et al (2012), and Zhang and He (2014), the authors suggested that "knowledge of the legal system and regulatory provisions, and tax subsidies for international investments or new business ventures is seriously essential for the managers of acquiring enterprises". Importantly, managers should aware local political setting, local government control, bureaucratic administration procedure, home and host country relations, trade agreements, and overall global business environment, together build special attention in achieving institutional dichotomous problems (Zhang and He, 2014).…”
Section: Recommendations For Business Managersmentioning
confidence: 99%
“…Importantly, managers should aware local political setting, local government control, bureaucratic administration procedure, home and host country relations, trade agreements, and overall global business environment, together build special attention in achieving institutional dichotomous problems (Zhang and He, 2014). Thus, managers must read and understand the legal terminology and relevant laws associated with specific industries prior to establishing their alliances or making acquisitions in countries like India.…”
Section: Recommendations For Business Managersmentioning
confidence: 99%
“…In a recent study, Serdar Dinc and Erel (2013) argued that "nationalism in mergers is more likely to be motivated by sociological and political reasons than economic ones". Therefore, host country regulations, policies, foreign relations between home and country countries and progress of the host country's economy are extremely essential for acquiring firm managers in successfully conducting overseas deals in emerging markets like India and China (e.g., Zhang & He, 2014). In addition, host country corruption is directly proportionate that adversely affects cross-border inward capital flows when coming from developed to developing economies (e.g., Barbopoulos, Marshall, MacInnes, & McColgan, 2014).…”
Section: External Factorsmentioning
confidence: 99%